Mystery Shopper as a Tool to Measure Staff Performance in Travel Agencies - Abdel Rady, Hussein Abdel Wahab (جامعة المنيا - كلية السياحة والفنادق, 2019)
المتسوق الخفي أن يقوم شخص ما بأداء خدمة معينة (تسوق – خدمة) دون الإفصاح عن هويته كمتسوق خفي ومن ثم يقوم بملأ استمارة استبيان بعد الانتهاء من عملية التسوق؛ هذا الاستبيان يحتوي أسئلة وإجاباتها عبارة عن اختيارات مثل هل قام الموظف بتحيتك؟ كم المدة التي استغرقتها عمليتك لإتمامها؟ وبعد الإجابة على كافة الأسئلة يأخذ هذا الفرع درجة معينة نقيس بها أداءه؛ مع مراعاة أن توزيع الأسئلة والدرجات تكون حسب الأهمية. تهدف هذه الورقة إلى تقييم مدي فائدة المتسوق الغامض لقياس أداء الموظفين، ودراسة وتقييم مهارات الاتصال لدي الموظفين من أجل تحديد نقاط ضعفهم وتحديد طريقة التحسين في شركات السياحة. والسبب هو أن قدراتهم ترتبط مع إدراك العميل الكلي لتقديم الخدمات. وقد اعتمدت الدراسة الميدانية على المنهج الوصفي التحليلي من خلال تصميم وتوزيع استمارات الاستبانة على عينة من المتسوقين الغامضين في شركات السياحة في الأقصر وأسوان وقد تم توزيع (۲۰۰) استمارة على عينة الدراسة. وتم استبعاد (٥٠) استمارة ليصبح إجمالي الاستمارات الصحيحة المستردة (١٥٠) استمارة بمعدل استجابة ٧٥%. وقد أظهرت نتائج الدراسة أن هناك علاقة إيجابية وهامه بين أراء المتسوق الخفي والأسباب المؤدية إلى التسوق الخفي، والمراقبة السرية والزيارة (تقييم الخدمات المقدمة من موظفي شركات السياحة إلى العملاء)، المكالمات الهاتفية، والبريد الإلكتروني/زيارة الموقع. وتوصى الدراسة بإخطار موظفي شركات السياحة بأنه يمكن التحقق من أدائهم من وقت لآخر من خلال المتسوق الخفي. يجب توضيح الأهداف والاستخدامات المقصودة من استخدام المتسوق الخفي لتقييم أداء موظفي شركات السياحة. Travel agencies operations rely to a great extent on measuring services quality, services delivered to their customers and measure whether staffs follow the visions of a company’s service quality standards. It then creates a feedback loop that allows companies to train their staff to consistently deliver services quality. Mystery shopping is a method that utilizes industry experts to assess services presented by travel agencies operations through living the real customer experience and engaging in normal customer - staff encounters and relations, leading to final assessment to be reported to concerned administration in order to optimize the overall performance. This paper aims to evaluate the advantages of the Mystery Shopper to measure staff performance, and assess communication skills of staffs in order to identify their weak points and define the way of Travel agencies’ development. The reason is that their applied abilities are connected with customer´s total perception of offering services. To achieve that, this research employed a method of descriptive analytical methodology by using a questionnaire tool. The sample was mystery shopper in Travel agencies. 200 questionnaires were administered; only (150) returned questionnaires were valid for the statistical manipulation of data with a response rate of 75% from the total distributed questionnaires to travel agencies in Luxor and Aswan. The results of the tools were analyzed using descriptive statistics, reliability analysis, coefficient analysis, and spearman correlation analysis with the support of SPSS 22.0. The research reached several results, there is a positive and significant relationship between Mystery shopping opinions and reasons performed of mystery shopper, Mystery observation and visit (Assess travel agencies staff provided service to customer), Mystery Telephone calls, and Mystery E-mail / Website Visit . The research recommended that Mystery Shopping objectively records travel agencies staff performance. Therefore the scope of a mystery shopping programme must include the variety of best conditions to measure staff performance.
Keywords: عملية التسويق -- برامج التسويق -- خدمات التسويق -- شركات السياحة